Rheumatoid Arthritis Saudi Database (RASD): Disease Characteristics and Remission Rates in a Tertiary Care Center - Almoallim H (Dove Medical Press, 2020)
Hani Almoallim,1– 3 Rola Hassan,2,3 Mohamed Cheikh,2,3 Hanan Faruqui,2 Reem Alquraa,2 Ayman Eissa,2 Aous Alhazmi,3 Roaa Alsolaimani,2,4 Nahed Janoudi2 1Department of Medicine, Faculty of Medicine, Umm Alqura University, Makkah, Saudi Arabia; 2Internal Medicine Department, Doctor Soliman Fakeeh Hospital, Jeddah, Saudi Arabia; 3Alzaidi Chair of Research in Rheumatic Diseases, Umm Alqura University, Makkah, Saudi Arabia; 4Department of Medicine, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Rola Hassan; Hani Almoallim Email r.toufiq@hotmail.com; hanialmoallim@gmail.comBackground: National Registries are essential to direct current practice. Rheumatoid arthritis (RA) registries in the middle east and North Africa remain scarcely represented.Objective: To describe a population of Saudi RA patients and to compare the findings to internationally reported data.Methods: This is an observational study that was conducted at Doctor Soliman Fakeeh Hospital (DSFH) in Saudi Arabia. The study ran from 2014 to 2018 using a pool of 433 patients. Inclusion criteria included adults older than 18 years of age who fulfilled the 2010 American College of Rheumatology criteria for the diagnosis of RA and who were also regular visitors in our rheumatology clinics. Data were collected directly from patients and entered in a specially designed program.Results: At initial presentation, 45.5% had demonstrated active disease (moderate or high disease activity) based on DAS-28-CRP scores, while 54.5% were in low disease activity or remission. The remission rates after 1 year had increased to 79.6% (345 patients), while 9.7% (42 patients) and 10.6% (46 patients) had low disease activity and moderate disease activity, respectively. It was also found that the female gender, higher Health Assessment Questionnaire-Disability Index (HAQ-DI) and longer lag1/lag2 periods were associated with higher disease activity in our population.Conclusion: We detected higher remission rates at 1 year of follow-up. This could be attributed to many factors, including good referral systems with easier access to biologics. We aim to expand this registry to the national level.Keywords: rheumatoid arthritis, disease-modifying antirheumatic drugs, biologics, TNF blockers, registry, remission rates